Latin American racial equality law as criminal law. Issue 3 (2nd September 2019) - Hernández, Tanya Katerí
ABSTRACT: After years of struggle for visibility, recognition, and equality in Latin America, Afro-descendants have garnered a number of anti-discrimination law enactments. These legal gains range from multi-cultural constitutional recognition, collective land titles, affirmative action programs and criminal sanctions on discrimination. Most pervasive across the region has been the deployment of anti-discrimination criminal law sanctions. This entry will examine the strengths and weaknesses of the criminal law model for addressing Afro-Latin American discrimination by focusing on a number of case examples from various countries.